Nas teias da ficção: espacialidades e visualidades em Antes do baile verde - Rezende, Rosana Gondim (2010)
This thesis proposes the study of spatialities and visualities observed in Before the green dance, anthology of Lygia Fagundes Telles. To this end, we selected some stories of this book, which, although very commonly known, had not yet been analyzed by this bias. The studies and analysis seek to focus, above all, the space in your physical and psychological, concrete and abstract nature. It is known that among the elements of narrative, space plays an important role; in an apparent function performs the task of the geographical location of characters, but his career in the fictional field goes far beyond this limit: it can give the reader clues to what will still occur, may be indicative of the character of the characters, can influence the behavior of the characters and be shaped by them, may favor the action, may be the door through which one enters the world of fiction. If closed, frames the narrative, emphasizing the character's fictional narrative if opened, its horizon reveals the social conflicts of being-in-world. While the characters integrate the statement, its characterization is part of the enunciation. Thus, the relationship between space and character exudes the atmosphere, narrative element significantly exploited by Lygia Fagundes Telles throughout his work. A strong ally of space on the work of Lygia Fagundes Telles is the senses, vehicle seizure of images. Among them, the vision shows itself sovereign. The visualities become, therefore, powerful support not only in the characterization of the place and characters but also the relationship between these two elements, promoting the referred atmosphere that, in the lygiana work, introduces the mystery, the unusual, the fantastic, the supernatural. The very title of the work, focused on this work, alludes to the visual as it gives a hue: "Before the green dance", a fact that opened path to us in the study of images and their representations. This trend culminated in the preparation of three chapters, namely: The sovereignty of the look in ―Come to see the setting sun‖, The space in the building of the fantastic in the short stories ―Christmas on the boat‖ and ―The chase‖ and The interlacing of images and spaces in ―Before the green dance and ―Yellow green lizard‖, where they are treated, respectively, these three discussions, indicating the literary wealth that the fiction space offers us.